Parrondoâs Paradox Based Strategies in The Serious Game of RTGS Using Sandpile Model - Bukhori, Saiful (Prosiding SNATIKA Vol 01 (2011), 2011)
This research proposed parrondoâs paradox strategies in the serious game of Real Time Gross Settlement using sandpile model, which develop the existence of the parrondo paradox and applied in serious game of RTGS as switching in the settlement process. The settlement process, that our proposed at this paper, is managed by clearing house. The mechanism at clearing house is a transmitter client sends a message of transaction through transmitter bank, that having canal at clearing house, then continue to receiver client through receiver bank by using sandpile model. When settlement process done by one transmitter bank (Process A), the probability of increase Net Worth (NW) is p. When settlement process done by more than one transmitter bank (Process B), we have introduced the probabilities of a self-transition in each state, that is, if the capital is a multiple of three we have a probability r1 of remaining in the same state, whereas if the capital is not a multiple of three then the probability is r2. We will turn to the random alternation of process A and B with probability Î³. This will be named as process AB. Examination result of process A change in net worth trend to decrease, process B trend to decrease and process AB that switches randomly between process A and process B trend to increase net worth. Simulation of parrondoâs paradox based strategies in the serious game RTGS using star logo by randomize process A and process B so distribution net worth lotÂ in the bank that has wealth in intermediate level, total money and total loan trend to rise, total saving loan trend to rise but total wallets trend to decrease. Â Kata Kunci: Parrondo paradox, RTGS, sandpile model, net worth.